Synovial CXCL3+FOSL2+ Macrophages Mediate Inflammation via FOSL2/AP-1 in Rheumatoid Arthritis: A Single-Cell Transcriptome Analysis - Wu, Yiwei; Yang, Jinming; Chen, Mengke; Chen, Xiaoxiang; Cao, Shan (International journal of molecular sciences, 2025)
Macrophages play a central role in joint inflammation and bone destruction in rheumatoid arthritis (RA). While activator protein-1 (AP-1) transcription factors have been implicated in RA pathogenesis, the specific roles of individual AP-1 members in regulating synovial macrophages remain unclear. To address this, two public single-cell transcriptomic datasets were first analyzed to profile synovial macrophages, and then to identify AP-1 family members and associated pathways via differential expression and gene set enrichment analyses. JUND, FOSL2, and FOSB were found to be highly enriched in the RA synovium, and a distinct CXCL3+FOSL2+ macrophage subset was identified, characterized by pro-inflammatory, metabolic, and differentiation-related pathways. Intercellular communication analysis further revealed that this CXCL3+FOSL2+ macrophage subset interacted with ACKR1+ endothelial cells within the synovial microenvironment. Validation in a large-cohort bulk transcriptomic dataset, together with functional assays using in vitro FOSL2 knockdown in U937 cell lines, further confirmed FOSL2’s role in promoting macrophage-driven inflammation. Collectively, these findings indicate that CXCL3+FOSL2+ macrophages drive RA synovitis via the FOSL2/AP-1 axis, highlighting a potential therapeutic target.